Soundscapes of Uyghur Islam - Harris, Rachel (Rachel A.) (Indiana University Press, 2020)
"China's Xinjiang Uyghur Autonomous Region is experiencing a crisis of securitization and mass incarceration. In Soundscapes of Uyghur Islam, author Rachel Harris examines the religious practice of a group of Uyghur women in a small village now engulfed in this chaos. Despite their remote location, these village women are mobile and connected, and their religious soundscapes flow out across transnational networks. Harris explores the spiritual and political geographies they inhabit, moving outward from the village to trace connections with Mecca, Istanbul, Bishkek, and Beijing. Sound, embodiment, and territoriality illuminate both the patterns of religious change among Uyghurs and the policies of cultural erasure used by the Chinese state to reassert its control over the land the Uyghurs occupy. By drawing on contemporary approaches to the circulation of popular music, Harris considers how various forms of Islam that arrive via travel and the Internet come into dialogue with local embodied practices. Synthesized together, these practices create new forms that facilitate powerful, affective experiences of faith"-- Provided by publisher
Keywords: Muslims -- China -- Xinjiang Uygur Zizhiqu -- Social conditions.; Muslim women -- China -- Xinjiang Uygur Zizhiqu -- Social conditions.; Uighur (Turkic people) -- China -- Xinjiang Uygur Zizhiqu -- Social life and customs.; Uighur (Turkic people) -- China -- Xinjiang Uygur Zizhiqu -- Music.; Xinjiang Uygur Zizhiqu (China) -- Ethnic relations.; China -- Ethnic relations.; Musulmans -- Chine -- Xinjiang -- Conditions sociales.; Musulmanes -- Chine -- Xinjiang -- Conditions sociales.; Ouïgour (Peuple turc) -- Chine -- Xinjiang -- Mœurs et coutumes.; Ouïgour (Peuple turc) -- Chine -- Xinjiang -- Musique.; Xinjiang (Chine) -- Relations interethniques.; RELIGION -- Islam -- Rituals & Practice.; Ethnic relations; Muslim women -- Social conditions; Muslims -- Social conditions; Uighur (Turkic people) -- Music; Uighur (Turkic people) -- Social life and customs; China; China -- Xinjiang Uygur Zizhiqu; Music